A numerical analysis of formation of the surface relief: A single inclusion model; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Zinovieva O. Olga; Romanova V. Varvara; Balokhonov R. R. Ruslan Revovich; Shakhijanov V. Valeriy; Emelyanova T. Tatiana (2014, 2014)
Title screen